On the determination of loop nature in the TEM - Jenkins, M; Fukushima, H; KirK, M (1997)
We have carried out systematic experiments to explore the range of applicability of the two direct methods which are available for the determination of the nature of small clusters. Experiments in heavy-ion irradiated silver and copper, including direct comparisons with the results of Black-White contrast analysis (B-W), forced us to the conclusion that use of the 2 1/2 D technique for the analysis of faulted loops is effectively impossible because of reciprocal-lattice spike and other effects. We used B-W analysis to investigate the nature of the clusters produced by room-temperature heavy-ion irradiation of copper. In-situ irradiations were performed in the Argonne HVEM-Tandem Facility using 40 keV and 80 keV Kr+ ions. Nearly all of the analysable first-layer loops were found to be vacancy in nature. Some deeper clusters were also certainly vacancy. There is no unequivocal evidence for interstitial loops under these conditions. The near impossibility of establishing that interstitial loops are not present is shown by the fact that a large fraction of loops - over 50 % - could not be analysed either because they did not display clear B-W contrast under any condition or sufficiently consistent B-W contrast under several different operating conditions.